2015
DOI: 10.1007/s00221-015-4210-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body posture on laterality judgement and explicit recognition tasks performed on self and others’ hands

Abstract: Judgments on laterality of hand stimuli are faster and more accurate when dealing with one's own than others' hand, i.e. the self-advantage. This advantage seems to be related to activation of a sensorimotor mechanism while implicitly processing one's own hands, but not during explicit one's own hand recognition. Here, we specifically tested the influence of proprioceptive information on the self-hand advantage by manipulating participants' body posture during self and others' hand processing. In Experiment 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 31 publications
8
20
0
Order By: Relevance
“…Previous studies on the hand laterality task performed on self or others' hands reported a self-advantage (Conson et al, 2015;Ferri et al, 2012;Ferri et al, 2011). This selfadvantage seems to be related to activation of left vPM that, instead, is not recruited when explicitly recognizing one's own hands (Ferri et al, 2012).…”
Section: Methodsmentioning
confidence: 76%
See 3 more Smart Citations
“…Previous studies on the hand laterality task performed on self or others' hands reported a self-advantage (Conson et al, 2015;Ferri et al, 2012;Ferri et al, 2011). This selfadvantage seems to be related to activation of left vPM that, instead, is not recruited when explicitly recognizing one's own hands (Ferri et al, 2012).…”
Section: Methodsmentioning
confidence: 76%
“…In Experiment 1 we did not find evidence of a self-advantage but speeded judgments on others' hands (i.e., self-disadvantage) during right EBA stimulation. Since previous behavioral experiments on explicit visual recognition of self and others' hands demonstrated a selfdisadvantage (Conson et al, 2015;Ferri et al, 2011; but see Conson, Aromino, & Trojano, 2010), in the present experiment, rTMS of right EBA and left vPM was applied to test whether stimulation of right EBA could also enhance explicit visual recognition of others' hands.…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…keeping a specific posture of one's own arms/hands) can affect behavioural performance on tasks implying motor simulation (e.g. the hand laterality task) in an effector-specific way, thus supporting a simulation view of motor imagery: more precisely, keeping a right (left) arm/hand in an awkward posture could impair participants' judgments on right (left)-hand stimuli with respect to comfortable hand postures (Conson et al 2011(Conson et al , 2015(Conson et al , 2016de Lange et al 2006;Ionta and Blanke 2009). We capitalized on these findings and assessed whether specific postures (i.e.…”
Section: Methodsmentioning
confidence: 98%